ASUHAN KEPERAWATAN PADA PASIEN GANGGUAN PERSEPSI HALUSINASI PENDENGARAN DENGAN PEMBERIAN TERAPI OKUPASI AKTIVITAS WAKTU LUANG DI YAYASAN REHABILITASI MENTAL GRIYA BHAKTI MEDIKA JAKARTA - Hairul Efendi; Ayu Pratiwi; Mukhamad Saeful (Nusantara Hasana Journal, 2024)
Hallucinations are defined as disturbances in a person's sensory perception, where there is no stimulus. One type of hallucination is auditory hallucinations (auditory-hearing voices or sounds). The impact caused by hallucinating patients is loss of self-control. To minimize the impact of hallucinations, one of the treatments is using occupational therapy, free time activities. Occupational therapy is the science and art of adapting the abilities that the patient once liked and possessed, directing a person's participation in carrying out certain tasks with the aim of restoring mental function. Objective: to determine the results of the application of occupational therapy in free time activities on signs and symptoms in patients with auditory hallucinations at the Griya Bakti Medika Jakarta Mental Rehabilitation Foundation. The design of this scientific work uses a case study method with a nursing process approach that focuses on optimizing nursing interventions for patients with auditory hallucination disorders. The results of the final scientific work of the nurses obtained an analysis of nursing care after the intervention was carried out for 3 days within ± 30 minutes. It was found that nursing actions and intervention innovations in Occupational Free Time Activities had positive results, the client's hallucinatory symptoms decreased and the client's ability to divert with Occupational free time activities. increases, clients are able to carry out interventions that are taught independently. One of the roles of nurses in dealing with hallucinations in patients at home and in hospitals is implementing Occupational Leisure Activity Intervention